Clinical and surgical evaluation of gynecomastia: tactic and results - Ferreira Filho, Darley de Lima; Ferreira, Nancy Cristina Ferraz de Lucena; Ferreira, Thais de Lucena (Mastology, 2020)
Objectives: To perform an assessment of the clinical and surgical characteristics of gynecomastia as a tactic used and the results obtained in the breast. Methods: A prospective and observational study was carried out in the mastology service of Hospital Barão de Lucena in 40 patients. To determine which factors are associated with the cosmetic outcome, the contingency table was constructed and the χ2 test for independence was applied. In cases in which the assumptions of the χ2 test were violated, Fisher’s exact test was applied. Results: Findings showed that most patients were from the metropolitan region of Recife (72.5%), studied until high school (62.5%), were aged 10 to 20 (42.5%), were in gynecomastia grade III (47.5%), underwent double incision (52.5%), had no complications (75.0%), and had a good and excellent cosmetic outcome (75.0%). The proportion comparison test was significant in all factors evaluated (p<0.05), except for the variable level of education (p=0.114), indicating that the numbers of patients who studied until high school and had higher education are close. The independence test was significant only in the variable complications (p<0.001), indicating that having complications significantly increases the risk for regular/bad cosmetics. Conclusion: Gynecomastia is a pathology of strong social impact. We observed this after analyzing the epidemiological, clinical, and surgical characteristics of our patients. In patients who underwent surgical treatment and who had no complications, there was a greater degree of satisfaction.